Moisture absorption and sweat releasing composite special-shaped chinlon 6 fiber as well as preparation method and application thereof

By adopting leather-core composite spinning process and multi-layer bath treatment in nylon 6 fibers, moisture-absorbent and perspiring composite nylon 6 fibers are prepared, which solves the problem of insufficient moisture-absorbent and perspiring performance of nylon 6 fibers in the prior art, and achieves more efficient sweat treatment and maintenance of mechanical properties.

CN119710976AActive Publication Date: 2025-03-28POLY PLASTIC MASTERBATCH SUZHOU

Patent Information

Application Number
CN202510220272.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-03-28
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

The prior art has limitations in improving the moisture-absorbing and perspiring performance of nylon 6 fiber, and it is difficult to meet the human body's sweating needs in strenuous exercise and sports competitions.

Method used

The skin-core composite spinning process is adopted, and the nylon 6 slices are used as the core layer raw material and the nylon 6 absorbent masterbatch containing calcium carbonate and boron nitride as the cortical raw material. The moisture-absorbing and perspiration composite nylon 6 fibers with a special cortical layer and a circular core layer are prepared by treating weak acid, weak alkali and a clean water bath.

Benefits of technology

It significantly improves the moisture-absorbing and sweating performance of the fiber, enhances the evaporation speed and wicking effect of sweat, meets the human body's sweating needs after strenuous exercise, and maintains the mechanical properties of the fiber.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710976A_ABST
    Figure CN119710976A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of functional fibers, and discloses a moisture-absorbing and sweat-releasing composite special-shaped chinlon 6 fiber and a preparation method and application thereof.The section of a skin layer of the moisture-absorbing and sweat-releasing composite special-shaped chinlon 6 fiber is in a three-leaf shape or a cross shape or a five-leaf shape, and the section of a core layer of the moisture-absorbing and sweat-releasing composite special-shaped chinlon 6 fiber is round; the preparation method comprises the following steps: by taking chinlon 6 slices as a core layer raw material and chinlon 6 absorbing and discharging master batches as a skin layer raw material, forming by adopting a skin-core composite spinning process to obtain fibers, sequentially soaking the fibers in a weak acid bath, a weak alkali bath and a clear water bath, taking out and drying to obtain the moisture-absorbing and sweat-releasing composite special-shaped chinlon 6 fibers, the chinlon 6 suction and discharge master batch is obtained by blending raw materials including chinlon 6 slices, boron nitride and calcium carbonate, and then melting, extruding and granulating through a double-screw extruder; according to the application, the prepared moisture absorption and sweat releasing composite special-shaped chinlon 6 fiber can be woven into a fabric. According to the invention, the mechanical property of the fiber is ensured, the moisture-conducting and sweat-discharging performance of the fiber is improved, and the sweat-discharging requirement of a human body after strenuous exercise can be met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of functional fibers and relates to a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber and a preparation method and application thereof. Background Art

[0002] Nylon, also widely known as "nylon", stands out among many synthetic fibers for its high strength, excellent wear resistance and excellent elasticity. Its wear resistance is particularly outstanding, making nylon fabrics extremely durable. At the same time, nylon also exhibits good elasticity and recoverability. Although it is easy to deform under the action of external forces, it can quickly return to its original shape during wearing. This feature makes it widely used in the field of sports equipment. Whether it is sportswear or sports shoes, nylon fibers can often be seen.

[0003] However, the moisture absorption and perspiration wicking performance of nylon is relatively weak, especially after strenuous exercise or competition, the wearer may feel hot and uncomfortable. To improve this situation, the industry often uses the method of spinning special-shaped fibers with special-shaped spinnerets, such as "T" type, "Y" type, "cross" type or "five-leaf" type, to enhance the moisture absorption and perspiration wicking ability of nylon.

[0004] Patent application with publication number CN102677215A discloses an antibacterial moisture-conducting nylon 6 and its preparation method, wherein the preparation method is to achieve the purpose of improving the moisture absorption and perspiration effect by spinning nylon 6 fibers with special-shaped cross-sections. Unfortunately, the improvement of its moisture absorption and perspiration performance is still limited by simply relying on the design of special-shaped cross-sections, and it is difficult to meet the perspiration needs of the human body during intense exercise, especially in sports competitions.

[0005] The patent application with publication number CN113337910A discloses a white graphene moisture absorption and perspiration cooling nylon staple fiber and its preparation method, wherein the preparation method is to directly spin boron nitride and nylon 6 into a "cross" type staple fiber after granulation, wherein the maximum addition amount of boron nitride can reach 14 wt%. However, due to the large amount of boron nitride filling, this method is only applicable to spinning nylon 6 staple fibers, and the mechanical properties of the resulting fibers are poor. Although the addition of boron nitride increases the evaporation rate of sweat, the conventional "cross" staple fiber has limited wicking effect on sweat, so the improvement of moisture absorption and perspiration effect is not significant.

[0006] The patent application with publication number CN105332089A discloses a method for preparing a moisture absorption and perspiration functional polyester fiber, wherein the preparation method is to add a high concentration of calcium carbonate masterbatch during the spinning process, and to prepare a porous "cross" polyester fiber by acid reaction after spinning, thereby improving the moisture absorption and perspiration performance of the fiber. However, this method also has the problem of filling a large amount of calcium carbonate, which leads to a decrease in the mechanical properties of the fiber. Although pores are formed on the fiber surface to enhance its wicking effect on sweat, overall, the improvement in the moisture absorption and perspiration effect is still limited.

[0007] Therefore, it is of great significance to study a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber and its preparation method and application to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to solve the problems existing in the prior art and to provide a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber and a preparation method and application thereof.

[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0010] A method for preparing a moisture-absorbing and perspiration-wicking composite special-shaped nylon 6 fiber, comprising: using nylon 6 slices as a core layer material, and nylon 6 absorbent and perspiration masterbatch as a skin layer material, forming the fiber by a skin-core composite spinning process, and then soaking the fiber in a weak acid bath, a weak alkali bath, and a clean water bath in sequence, taking it out and drying it to obtain the moisture-absorbing and perspiration-wicking composite special-shaped nylon 6 fiber;

[0011] The pH value of the weak acid bath is greater than 5 and less than 7, and the temperature is 30~50℃; the pH value of the weak base bath is greater than 7 and less than 9, and the temperature is 30~50℃; the pH value of the water bath is 7, and the temperature is 30~50℃; weak acid bath: the temperature of 30~50℃ is conducive to the dissolution and removal of the reaction products. For example, when using an acetic acid bath, within this temperature range, the degree of ionization of acetic acid is relatively appropriate, and it can better react with residual calcium salts and other substances to form soluble acetates and be removed. At the same time, the appropriate temperature can make the fiber molecular segments have certain activity, which is conducive to the adjustment of the fiber structure. If the temperature is too low, the reaction rate will be very slow and the efficiency of removing impurities will be low; too high a temperature may damage the fiber, because some properties of the fiber (such as strength, elasticity, etc.) may deteriorate under the combined action of high temperature and acidic environment. Weak base bath: Taking an ammonia bath as an example, at 30~50℃, the ionization equilibrium of ammonia water is conducive to the reaction of OH⁻ ions with residual acid ions. For example, at this temperature, the acidic substances remaining on the fiber surface can be better neutralized to generate water and corresponding salts, thereby cleaning the fiber surface. Moreover, the appropriate temperature can make the interaction between the weak base and the fiber more effective, which is helpful for improving the feel and other properties of the fiber. If the temperature is too low, the reaction between the alkali and the impurities will not be sufficient; if the temperature is too high, it may cause changes in the chemical structure of the fiber, such as hydrolysis, and will also increase energy consumption. Clean water bath: A clean water bath at 30~50℃ is mainly used for cleaning. This temperature is slightly higher than normal temperature, which can speed up the diffusion of residual substances on the fiber surface and make the cleaning more thorough. Because the temperature rises, the molecular movement speeds up, whether it is the impurity molecules on the fiber surface or the solvent molecules in the water, their movement speed increases, which is more conducive to the impurities entering the water from the fiber surface and being taken away.

[0012] Considering the physical properties of the fiber, treating the fiber in a bath at 30~50℃ can keep the fiber in good dimensional stability. Within this temperature range, the fiber will not shrink or expand excessively due to excessive temperature, ensuring that the shape and size of the fiber remain basically unchanged. If the temperature exceeds this range, it may cause thermal shrinkage of the fiber, change the physical properties of the fiber, and affect subsequent use. At the same time, this temperature range helps to maintain the flexibility of the fiber. For most fibers, too low a temperature will make the fiber brittle, and too high a temperature may cause the fiber to lose its elasticity. After being treated in a bath at 30~50℃, the fiber can maintain good flexibility, which is very important for textile processing (such as weaving, knitting, etc.) and the performance of the final product (such as wearing comfort).

[0013] Nylon 6 suction and discharge masterbatch is made of nylon 6 chips, boron nitride and calcium carbonate as raw materials, which are blended and granulated by melt extrusion through a twin-screw extruder.

[0014] After being treated in a weak acid bath, the weak acid will react with a large amount of calcium carbonate on the fiber surface to leave micropores, greatly increasing the specific surface area of ​​the special-shaped fiber, thereby enhancing the moisture absorption and perspiration effect. The fiber cortex is added with nylon 6 masterbatch containing calcium carbonate and boron nitride. The masterbatch is melt-dispersed and extruded by a twin-screw extruder, so the boron nitride can be evenly dispersed around the calcium carbonate, and because boron nitride has a thermal conductivity effect, the heat transfer inside the fiber is more efficient, and the number and uniformity of micropores are significantly increased.

[0015] As the preferred technical solution:

[0016] In the method for preparing the moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber as described above, the mass ratio of the skin layer raw material to the core layer raw material is 10-30:70-90.

[0017] The method for preparing the moisture-absorbing and perspiration-wicking composite special-shaped nylon 6 fiber as described above has the following spinning process parameters: spinning temperature 240~270°C, spinning speed 4500~6000 m / min, side blowing temperature 15~25°C, side blowing speed 0.3~0.8 m / s, and oiling rate 0.6~1.2%.

[0018] The method for preparing a moisture wicking composite special-shaped nylon 6 fiber as described above, wherein the weak acid bath is an acetic acid bath, a citric acid bath or a formic acid bath, and the fiber is immersed in the weak acid bath for 10 to 30 seconds;

[0019] The weak alkali bath is an ammonia bath, a sodium bicarbonate bath or a triethanolamine bath, and the fiber is immersed in the weak alkali bath for 10 to 30 seconds;

[0020] The fiber is immersed in the water bath for 60 to 120 seconds;

[0021] The drying temperature is 80~100℃.

[0022] The preparation method of the moisture-absorbing and perspiration-wicking composite special-shaped nylon 6 fiber as described above, the specific preparation process of the nylon 6 moisture-absorbing and perspiration-wicking masterbatch is as follows: according to the mass proportions, 72-90 parts of nylon 6 slices, 5-10 parts of boron nitride, 5-15 parts of calcium carbonate and 0-3 parts of dispersant are put into a high-speed mixer and mixed evenly, and the evenly mixed materials are added into a twin-screw extruder for melt extrusion granulation to obtain the nylon 6 moisture-absorbing and perspiration-wicking masterbatch.

[0023] In the method for preparing the moisture wicking composite special-shaped nylon 6 fiber as described above, the rotation speed of the high-speed mixer is 500-1000 rpm, the mixing time is 5-20 min; and the extrusion temperature is 200-270°C.

[0024] The method for preparing a moisture wicking composite shaped nylon 6 fiber as described above, wherein the average flake diameter of the boron nitride is 1-2 μm and the thickness is 10 nm;

[0025] The average particle size of calcium carbonate is 80nm;

[0026] The dispersant is one or more of ethylene bisstearic acid amide, ethylene acrylic acid copolymer and ethylene acrylic acid copolymer zinc salt ionomer.

[0027] The present invention also provides a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber prepared by the method described in any one of the above items, wherein the cross section of the cortex is a "three-leaf" type, a "cross" type or a "five-leaf" type, and the cross section of the core layer is a circle.

[0028] As the preferred technical solution:

[0029] The moisture-absorbing and perspiration-wicking composite shaped nylon 6 fiber as described above has a breaking strength of 3.70-3.75 cN / tex, a number of micropores per unit area (2 μm×2 μm) on the fiber surface of 80-120, and a micropore size deviation of no more than 10%.

[0030] The present invention also provides an application of a moisture-absorbing and perspiration-wicking composite special-shaped nylon 6 fiber as described in any of the above items, which is used to weave fabrics; after the fibers are formed by a core-skin composite spinning process, the fibers are first made into fabrics, and then the fabrics are sequentially immersed in a weak acid bath, a weak alkali bath, and a clean water bath, and the treatment efficiency is relatively higher;

[0031] The water absorption rate of the fabric is 270~290%, the drip diffusion time is 0.2~0.6s, the wicking height is 180~220mm, and the drying rate is 0.8~1.3g / h.

[0032] Principle of the invention:

[0033] The moisture-absorbing and perspiration-wicking composite special-shaped nylon 6 fiber of the present invention has a circular core layer cross section, and conventional nylon 6 slices are added to support and improve the spinnability, thereby ensuring the mechanical properties of the fiber; the cross section of the skin layer is special-shaped, and a high-concentration moisture-absorbing and perspiration-wicking masterbatch can be added. The fiber skin layer is added with a nylon 6 masterbatch containing calcium carbonate and boron nitride, and the masterbatch is melt-dispersed and extruded by a twin-screw extruder, so the boron nitride can be evenly dispersed around the calcium carbonate; the addition of boron nitride significantly enhances the thermal conductivity of the fiber, making the heat transfer inside the fiber more efficient. Therefore, when the spun-formed fiber is immersed in a weak acid bath, the heat transfer of the weak acid bath is more uniform, so that the contact reaction between the acid and calcium carbonate is more sufficient and uniform, avoiding the uneven reaction phenomenon caused by excessively high or low local temperature. Therefore, on the one hand, the reaction time can be greatly shortened when other conditions remain unchanged, the fiber pore-making efficiency is higher, and the number of micropores per unit area on the fiber surface can be greatly increased. The more micropores there are, the faster the diffusion and evaporation of water, and the better the moisture absorption and perspiration performance; on the other hand, the size of the generated pores is closer, and the uniformity of the pores is significantly improved, which greatly improves the fiber's wicking effect on sweat (the reason why the improvement of pore uniformity can enhance the wicking effect is as follows: 1. Stability of the liquid transmission path: When the micropores on the fiber surface are more uniform, the liquid transmission path on the fiber surface is more regular and stable. This is like transporting liquid in a well-planned pipeline system. The liquid can flow along the evenly distributed micropores and fiber gaps in a relatively stable manner. 1. Avoid local accumulation: Uniform micropores can prevent local accumulation of liquid on the fiber surface. If the micropores are uneven, liquid may accumulate in areas with larger or more micropores, and be difficult to transmit in areas with smaller or fewer micropores. This is like in a system with uneven heights and uneven pipe thickness, liquid tends to accumulate in low-lying or thick pipes. Uniform micropores can evenly distribute liquid on the fiber surface, ensuring that the wicking process can be carried out efficiently. Therefore, the more uniform the micropores on the fiber surface, the better the wicking effect is generally).

[0034] Therefore, through this special design of the present invention, the mechanical properties of the fiber are guaranteed, and the moisture conduction and perspiration discharge performance of the fiber is greatly improved, thereby meeting the perspiration needs of the human body after intense exercise.

[0035] Beneficial effects:

[0036] (1) The present invention uses nylon 6 slices as the core layer material and designs the core layer cross-section of the fiber to be circular, which can play a role in supporting and improving the spinnability, thereby ensuring the mechanical properties of the fiber.

[0037] (2) The cortical cross-section of the fiber of the present invention is irregular, and nylon 6 absorption and discharge masterbatch is used as the raw material. The nylon 6 absorption and discharge masterbatch is extruded by a twin-screw melt dispersion, so that the boron nitride can be evenly dispersed around the calcium carbonate, which significantly enhances the thermal conductivity of the fiber and makes the heat transfer inside the fiber more efficient. As a result, when the spun fiber is immersed in a weak acid bath, the heat transfer of the weak acid bath is more uniform, avoiding the uneven reaction phenomenon caused by local excessively high or low temperature. Ultimately, the number of micropores per unit area on the fiber surface is greatly increased, the size of the pores is more uniform, and the wicking effect on sweat is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 It is a schematic cross-sectional view of the moisture wicking composite special-shaped nylon 6 fiber prepared in Example 1 of the present invention;

[0039] Figure 2 It is a schematic cross-sectional view of the moisture wicking composite shaped nylon 6 fiber prepared in Example 2 of the present invention;

[0040] Figure 3 It is a schematic cross-sectional view of the moisture wicking composite special-shaped nylon 6 fiber prepared in Example 3 of the present invention;

[0041] Among them, 1-cortex, 2-core. DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0043] In order to ensure that the properties of the materials used in each embodiment and comparative example are fully disclosed, the manufacturers and brands of the materials are indicated, and products of other manufacturers and brands that meet the requirements of the present invention are also feasible.

[0044] The testing methods of the relevant performance indicators in the following embodiments and comparative examples are as follows:

[0045] Breaking strength: the breaking strength of the fibers prepared in each embodiment and each comparative example was tested with reference to GB / T 14344-2022 “Test method for tensile properties of chemical fiber filaments”.

[0046] Water absorption rate, drip diffusion time, wicking height and drying rate: refer to GB / T 21655.1-2023 "Evaluation of moisture absorption and quick-drying properties of textiles Part 1: Single combination test method" standard to test the water absorption rate, drip diffusion time, wicking height and drying rate of the fabrics prepared in each embodiment and each comparative example.

[0047] Example 1

[0048] A method for preparing a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber, comprising the following steps:

[0049] (1) Preparation of nylon 6 absorption and discharge masterbatch;

[0050] According to the mass proportion, 79 parts of nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400), 10 parts of boron nitride (average sheet diameter: 1 μm, thickness: 10 nm), 10 parts of calcium carbonate (average particle size: 80 nm) and 1 part of dispersant (ethylene bisstearamide) were put into a high-mixer and mixed evenly. The evenly mixed materials were added into a twin-screw extruder for melt extrusion granulation to obtain nylon 6 suction and discharge masterbatch; wherein, the high-mixer The speed of the machine is 800rpm, and the mixing time is 10min; in the twin-screw extruder, the temperature of zone 1 is 240℃, the temperature of zone 2 is 270℃, the temperature of zone 3 is 270℃, the temperature of zone 4 is 270℃, the temperature of zone 5 is 260℃, the temperature of zone 6 is 260℃, the temperature of zone 7 is 240℃, the temperature of zone 8 is 200℃, the temperature of zone 9 is 200℃, the temperature of zone 10 is 200℃, the temperature of zone 11 is 220℃, and the temperature of zone 12 is 250℃;

[0051] (2) Using nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400) as the core layer raw material and nylon 6 absorption and discharge masterbatch as the skin layer raw material, the skin-core composite spinning process was used to form the fiber; wherein the mass ratio of the skin layer raw material to the core layer raw material was 10:90;

[0052] The spinning process parameters are: spinning temperature 270°C, spinning speed 4500m / min, side blowing temperature 15°C, side blowing speed 0.4m / s, oiling rate 0.6%;

[0053] (3) The fiber obtained in step (2) is first soaked in a citric acid solution at 30°C and pH 6 for 20 seconds, then soaked in a sodium bicarbonate solution at 30°C and pH 8 for 20 seconds, and finally soaked in a clean water bath at 30°C and pH 7 for 100 seconds. After being taken out, the fiber is dried at 80°C to obtain a moisture wicking composite shaped nylon 6 fiber.

[0054] like Figure 1As shown, the cross-section of the cortex 1 of the moisture wicking composite shaped nylon 6 fiber finally obtained is a "three-leaf" type, and the cross-section of the core layer 2 is circular; the breaking strength of the moisture wicking composite shaped nylon 6 fiber is 3.71 cN / tex, the number of micropores per unit area (2μm×2μm) on the fiber surface is 81, and the micropore size deviation is 6%.

[0055] The moisture wicking composite special-shaped nylon 6 fiber prepared above is made into fabric by weft knitting process;

[0056] The final fabric has a warp density of 100 strands / inch, a weft density of 80 strands / inch, a water absorption rate of 280%, a drip diffusion time of 0.6s, a wicking height of 185mm, and a drying rate of 0.82g / h.

[0057] Comparative Example 1

[0058] A method for preparing a special-shaped nylon 6 fiber is basically the same as that in Example 1, except that: step (1) is not performed, in step (2), only nylon 6 slices are used as raw materials, and the fiber is prepared by a conventional spinning assembly, and the fiber used in step (3) is prepared in this comparative example.

[0059] The number of micropores per unit area (2 μm×2 μm) on the fiber surface of the finally obtained shaped nylon 6 fiber was 0.

[0060] The above-prepared shaped nylon 6 fiber is woven into a fabric, and the preparation process is basically the same as that of Example 1, except that the fiber used is the shaped nylon 6 fiber prepared in this comparative example.

[0061] The final fabric has a water absorption rate of 141%, a drip diffusion time of 3.1s, a wicking height of 106mm, and a drying rate of 0.35g / h.

[0062] By comparing Comparative Example 1 with Example 1, it can be seen that the moisture absorption and perspiration performance of the fabric prepared in Comparative Example 1 is significantly reduced. This is because although Comparative Example 1 and Example 1 also spun shaped nylon 6 fibers, Example 1 formed a large number of micropores on the fiber surface, which greatly increased the specific surface area of ​​the fiber, thereby improving the moisture absorption and perspiration performance of the fabric.

[0063] Comparative Example 2

[0064] A method for preparing special-shaped nylon 6 fibers is basically the same as that in Example 1, except that in step (2), nylon 6 slices and the nylon 6 absorption and discharge masterbatch obtained in step (1) are directly mixed to prepare the fibers.

[0065] The breaking strength of the final shaped nylon 6 fiber is 2.79 cN / tex, the number of micropores per unit area (2μm×2μm) on the fiber surface is 67, and the micropore size deviation is 10%.

[0066] The above-prepared shaped nylon 6 fiber is woven into a fabric, and the preparation process is basically the same as that of Example 1, except that the fiber used is the shaped nylon 6 fiber prepared in this comparative example.

[0067] The final fabric has a water absorption rate of 252%, a drip diffusion time of 1.5s, a wicking height of 162mm, and a drying rate of 0.61g / h.

[0068] Comparing Comparative Example 2 with Example 1, it can be seen that the breaking strength and micropore number of the special-shaped nylon 6 fiber prepared in Comparative Example 2 are reduced, and the moisture absorption and perspiration performance of the fabric prepared therefrom is poor. This is because in Comparative Example 2, the nylon 6 slices and the nylon 6 absorption and perspiration masterbatch are directly mixed and spun, which makes the nylon 6 absorption and perspiration masterbatch evenly distributed throughout the fiber, and the carrier resin in the nylon 6 absorption and perspiration masterbatch distributed inside the fiber is severely degraded after the second high-temperature processing, resulting in a wide distribution of the molecular weight of the nylon 6 resin in the whole nylon 6 fiber, which greatly reduces the breaking strength of the whole nylon 6 fiber. In addition, since the comparative example 2 adds the nylon 6 absorption and drainage masterbatch evenly to the whole fiber, the calcium carbonate and boron nitride therein are also evenly distributed in the whole fiber, while the calcium carbonate and boron nitride in the embodiment 1 are only distributed in the cortical fiber part. Therefore, when the fiber thickness and shape are the same, theoretically, the boron nitride and calcium carbonate on the fiber surface will be less when the nylon 6 absorption and drainage masterbatch is added to the whole fiber, resulting in a decrease in the number of surface micropores and specific surface area of ​​the obtained moisture absorption and perspiration composite shaped nylon 6 fiber, which in turn leads to a significant decrease in the moisture absorption and perspiration effect of the fabric prepared therefrom.

[0069] Comparative Example 3

[0070] A method for preparing composite shaped nylon 6 fiber is basically the same as that in Example 1, except that the calcium carbonate in step (1) is replaced by an equal mass of boron nitride.

[0071] The number of micropores per unit area (2 μm×2 μm) on the fiber surface of the composite shaped nylon 6 fiber finally obtained was 0.

[0072] The composite shaped nylon 6 fiber prepared as above is woven into a fabric, and the preparation process is basically the same as that in Example 1, except that the fiber used is the composite shaped nylon 6 fiber prepared in this comparative example.

[0073] The final fabric has a water absorption rate of 193%, a drip diffusion time of 2.2s, a wicking height of 115mm, and a drying rate of 0.43g / h.

[0074] By comparing Comparative Example 3 with Example 1, it can be seen that the number of micropores per unit area on the fiber surface of the composite shaped nylon 6 fiber prepared in Comparative Example 3 is 0, and the moisture absorption and perspiration effect of the fabric prepared therefrom is reduced. This is because Comparative Example 3 does not introduce calcium carbonate into the fiber cortex, resulting in no micropores on the surface of the prepared composite shaped nylon 6 fiber, and its specific surface area is low, so the moisture absorption and perspiration effect of the fabric prepared therefrom is greatly reduced.

[0075] Comparative Example 4

[0076] A method for preparing composite shaped nylon 6 fiber is basically the same as that in Example 1, except that the boron nitride in step (1) is replaced by an equal mass of calcium carbonate.

[0077] The number of micropores per unit area (2 μm×2 μm) on the fiber surface of the composite shaped nylon 6 fiber finally obtained is 42, and the micropore size deviation is 53%.

[0078] The composite shaped nylon 6 fiber prepared as above is woven into a fabric, and the preparation process is basically the same as that in Example 1, except that the fiber used is the composite shaped nylon 6 fiber prepared in this comparative example.

[0079] The final fabric has a water absorption rate of 204%, a drip diffusion time of 2s, a wicking height of 120mm, and a drying rate of 0.45g / h.

[0080] By comparing Comparative Example 4 with Example 1, it can be seen that the number of micropores per unit area on the surface of the composite shaped nylon 6 fiber prepared in Comparative Example 4 decreases, and the deviation of the micropore size increases significantly, and the moisture absorption and perspiration performance of the fabric prepared therefrom decreases. This is because boron nitride has thermal conductivity, and Comparative Example 4 does not introduce boron nitride into the fiber cortex, which will cause the composite shaped nylon 6 fiber prepared in this comparative example to transfer heat slowly when immersed in a weak acid bath, resulting in problems such as local temperatures being too low or too high, and uneven reaction, which leads to a decrease in the number of micropores per unit area and a significant increase in the deviation of the micropore size, and the moisture absorption and perspiration performance of the fabric prepared therefrom is significantly reduced.

[0081] Example 2

[0082] A method for preparing a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber, comprising the following steps:

[0083] (1) Preparation of nylon 6 absorption and discharge masterbatch;

[0084] According to the weight ratio, 72 parts of nylon 6 slices (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400), 10 parts of boron nitride (average slice diameter: 1.5 μm, thickness: 10 nm), 15 parts of calcium carbonate (average particle size: 80 nm) and 3 parts of ethylene acrylic acid copolymer (manufacturer: Honeywell International, model: Honeywell ethylene-acrylic acid (EAA) copolymer wax powder AC® 580) is put into a high-speed mixer and mixed evenly, and the evenly mixed materials are added to a twin-screw extruder for melt extrusion granulation to obtain nylon 6 suction and discharge masterbatch; wherein, the speed of the high-speed mixer is 1000rpm, and the mixing time is 20min; the temperature of the first zone of the twin-screw extruder is 240℃, the temperature of the second zone is 270℃, the temperature of the third zone is 270℃, the temperature of the fourth zone is 270℃, the temperature of the fifth zone is 260℃, the temperature of the sixth zone is 260℃, the temperature of the seventh zone is 240℃, the temperature of the eighth zone is 200℃, the temperature of the ninth zone is 200℃, the temperature of the tenth zone is 200℃, the temperature of the eleventh zone is 220℃, and the temperature of the twelveth zone is 250℃;

[0085] (2) Nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400) were used as the core layer raw material, and nylon 6 absorption and discharge masterbatch was used as the skin layer raw material, and the skin-core composite spinning process was used to form the fiber; wherein the mass ratio of the skin layer raw material to the core layer raw material was 30:70;

[0086] The spinning process parameters are: spinning temperature 270°C, spinning speed 4500m / min, side blowing temperature 15°C, side blowing speed 0.3m / s, oiling rate 0.6%;

[0087] (3) The fiber obtained in step (2) is first soaked in a citric acid solution at 40°C and pH 5.5 for 30 seconds, then soaked in a sodium bicarbonate solution at 40°C and pH 8.5 for 30 seconds, and finally soaked in a clean water bath at 50°C and pH 7 for 60 seconds. After being taken out, the fiber is dried at 80°C to obtain a moisture wicking composite shaped nylon 6 fiber.

[0088] like Figure 2 As shown, the cross-section of the cortex 1 of the moisture wicking composite shaped nylon 6 fiber finally obtained is a "cross" shape, and the cross-section of the core layer 2 is a circle; the breaking strength of the moisture wicking composite shaped nylon 6 fiber is 3.73 cN / tex, the number of micropores per unit area (2μm×2μm) on the fiber surface is 120, and the micropore size deviation is 7%.

[0089] The moisture absorption and perspiration-releasing composite special-shaped nylon 6 fiber prepared above is made into fabric by using a weft knitting process.

[0090] The final fabric has a warp density of 110 strands / inch, a weft density of 90 strands / inch, a water absorption rate of 275%, a drip diffusion time of 0.5s, a wicking height of 183mm, and a drying rate of 0.81g / h.

[0091] Example 3

[0092] A method for preparing a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber, comprising the following steps:

[0093] (1) Preparation of nylon 6 absorption and discharge masterbatch;

[0094] According to the weight ratio, 85.5 parts of nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400), 8 parts of boron nitride (average sheet diameter: 1 μm, thickness: 10 nm), 5 parts of calcium carbonate (average particle size: 80 nm) and 1.5 parts of zinc salt ionomer of ethylene acrylic acid copolymer (manufacturer: Honeywell International, model: Honeywell AClyn®) were mixed. 295A) is put into a high-speed mixer for uniform mixing, and the uniformly mixed materials are added to a twin-screw extruder for melt extrusion granulation to obtain nylon 6 suction and discharge masterbatch; wherein, the speed of the high-speed mixer is 500rpm, and the mixing time is 5min; the temperature of the first zone of the twin-screw extruder is 240℃, the temperature of the second zone is 270℃, the temperature of the third zone is 270℃, the temperature of the fourth zone is 270℃, the temperature of the fifth zone is 260℃, the temperature of the sixth zone is 260℃, the temperature of the seventh zone is 240℃, the temperature of the eighth zone is 200℃, the temperature of the ninth zone is 200℃, the temperature of the tenth zone is 200℃, the temperature of the eleventh zone is 220℃, and the temperature of the twelveth zone is 250℃;

[0095] (2) Nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400) were used as the core layer raw material, and nylon 6 absorption and discharge masterbatch was used as the skin layer raw material, and the skin-core composite spinning process was used to form the fiber; wherein the mass ratio of the skin layer raw material to the core layer raw material was 20:80;

[0096] The spinning process parameters are: spinning temperature 270°C, spinning speed 6000m / min, side blowing temperature 25°C, side blowing speed 0.8m / s, oiling rate 1.2%;

[0097] (3) The fiber obtained in step (2) is first soaked in a formic acid solution at 50°C and a pH value of 5.8 for 10 seconds, then soaked in a triethanolamine solution at 50°C and a pH value of 8.2 for 10 seconds, and finally soaked in a clean water bath at 30°C and a pH value of 7 for 120 seconds. After being taken out, the fiber is dried at 90°C to obtain a moisture wicking composite shaped nylon 6 fiber.

[0098] like Figure 3As shown, the cross-section of the cortex 1 of the moisture wicking composite shaped nylon 6 fiber finally obtained is a "five-leaf" type, and the cross-section of the core layer 2 is circular; the breaking strength of the moisture wicking composite shaped nylon 6 fiber is 3.72 cN / tex, the number of micropores per unit area (2μm×2μm) on the fiber surface is 80, and the micropore size deviation is 5%.

[0099] The moisture absorption and perspiration-releasing composite special-shaped nylon 6 fiber prepared above is made into fabric by using a weft knitting process.

[0100] The final fabric has a warp density of 125 strands / inch, a weft density of 100 strands / inch, a water absorption rate of 270%, a drip diffusion time of 0.4s, a wicking height of 180mm, and a drying rate of 0.8g / h.

[0101] Example 4

[0102] A method for preparing a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber, comprising the following steps:

[0103] (1) Preparation of nylon 6 absorption and discharge masterbatch;

[0104] According to the weight ratio, 81 parts of nylon 6 chips (manufactured by Guangdong Hengshen Meida New Materials Co., Ltd., brand M2400), 10 parts of boron nitride (average flake diameter of 2 μm, thickness of 10 nm), 8 parts of calcium carbonate (average particle size of 80 nm) and 1 part of dispersant (ethylene bis stearamide and ethylene acrylic acid copolymer in a mass ratio of 1:1, the manufacturer of ethylene acrylic acid copolymer is Honeywell International, model Honeywell ethylene-acrylic acid (EAA) copolymer wax powder AC® 580) is put into a high-speed mixer and mixed evenly, and the evenly mixed materials are added to a twin-screw extruder for melt extrusion granulation to obtain nylon 6 suction and discharge masterbatch; wherein, the speed of the high-speed mixer is 500rpm, and the mixing time is 10min; the temperature of the first zone in the twin-screw extruder is 240℃, the temperature of the second zone is 270℃, the temperature of the third zone is 270℃, the temperature of the fourth zone is 270℃, the temperature of the fifth zone is 260℃, the temperature of the sixth zone is 260℃, the temperature of the seventh zone is 240℃, the temperature of the eighth zone is 200℃, the temperature of the ninth zone is 200℃, the temperature of the tenth zone is 200℃, the temperature of the eleventh zone is 220℃, and the temperature of the twelveth zone is 250℃;

[0105] (2) Using nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400) as the core layer raw material and nylon 6 absorption and discharge masterbatch as the skin layer raw material, the skin-core composite spinning process was used to form the fiber; wherein the mass ratio of the skin layer raw material to the core layer raw material was 10:90;

[0106] The spinning process parameters are: spinning temperature 270°C, spinning speed 5300m / min, side blowing temperature 20°C, side blowing speed 0.5m / s, oiling rate 0.9%;

[0107] (3) The fiber obtained in step (2) is first soaked in an acetic acid solution at 35°C and a pH value of 6.5 for 20 seconds, then soaked in an ammonia solution at 35°C and a pH value of 7.5 for 20 seconds, and finally soaked in a clean water bath at 40°C and a pH value of 7 for 90 seconds. After being taken out, it is dried at 100°C to obtain a moisture wicking composite shaped nylon 6 fiber.

[0108] The final moisture-absorbing and perspiration-wicking composite shaped nylon 6 fiber has a cortical cross-section of a "three-leaf" type and a core cross-section of a circular type; the breaking strength of the moisture-absorbing and perspiration-wicking composite shaped nylon 6 fiber is 3.75 cN / tex, the number of micropores per unit area (2μm×2μm) on the fiber surface is 100, and the micropore size deviation is 4%.

[0109] The moisture absorption and perspiration-releasing composite special-shaped nylon 6 fiber prepared above is made into fabric by using a weft knitting process.

[0110] The final fabric has a warp density of 140 strands / inch, a weft density of 110 strands / inch, a water absorption rate of 290%, a drip diffusion time of 0.6s, a wicking height of 220mm, and a drying rate of 1.3g / h.

[0111] Example 5

[0112] A method for preparing a moisture absorbing and perspiration wicking composite special-shaped nylon 6 fiber, comprising the following steps:

[0113] (1) Preparation of nylon 6 absorption and discharge masterbatch;

[0114] According to the mass fraction, 90 parts of nylon 6 slices (manufacturer is Guangdong Hengshen Meida New Materials Co., Ltd., brand M2400), 5 parts of boron nitride (average sheet diameter is 1.5 μm, thickness is 10 nm) and 5 parts of calcium carbonate (average particle size is 80 nm) are put into a high-speed mixer and mixed evenly, and the evenly mixed materials are added to a twin-screw extruder for melt extrusion granulation to obtain nylon 6 suction and discharge masterbatch; wherein, the speed of the high-speed mixer is 700 rpm, and the mixing time is 20 min; the temperature of the first zone in the twin-screw extruder is 240°C, the temperature of the second zone is 270°C, the temperature of the third zone is 270°C, the temperature of the fourth zone is 270°C, the temperature of the fifth zone is 260°C, the temperature of the sixth zone is 260°C, the temperature of the seventh zone is 240°C, the temperature of the eighth zone is 200°C, the temperature of the ninth zone is 200°C, the temperature of the tenth zone is 200°C, the temperature of the eleventh zone is 220°C, and the temperature of the twelfth zone is 250°C;

[0115] (2) Nylon 6 chips (manufacturer: Guangdong Hengshen Meida New Materials Co., Ltd., brand: M2400) were used as the core layer raw material, and nylon 6 suction and discharge masterbatch was used as the skin layer raw material, and the skin-core composite spinning process was used to form the fiber; wherein the mass ratio of the skin layer raw material to the core layer raw material of the spinneret hole was 20:80;

[0116] The spinning process parameters are: spinning temperature 270°C, spinning speed 6000m / min, side blowing temperature 20°C, side blowing speed 0.5m / s, oiling rate 1.2%;

[0117] (3) The fiber obtained in step (2) is first soaked in a formic acid solution at 40°C and a pH value of 6.3 for 10 seconds, then soaked in a triethanolamine solution at 40°C and a pH value of 7.7 for 10 seconds, and finally soaked in a clean water bath at 35°C and a pH value of 7 for 100 seconds. After being taken out, the fiber is dried at 100°C to obtain a moisture wicking composite shaped nylon 6 fiber.

[0118] The final moisture-absorbing and perspiration-wicking composite shaped nylon 6 fiber has a cortical cross-section of a "five-leaf" type and a core cross-section of a circular type; the breaking strength of the moisture-absorbing and perspiration-wicking composite shaped nylon 6 fiber is 3.73 cN / tex, the number of micropores per unit area (2μm×2μm) on the fiber surface is 92, and the micropore size deviation is 4%.

[0119] The moisture absorption and perspiration-releasing composite special-shaped nylon 6 fiber prepared above is made into fabric by using a weft knitting process.

[0120] The final fabric has a warp density of 150 strands / inch, a weft density of 120 strands / inch, a water absorption rate of 273%, a drip diffusion time of 0.2s, a wicking height of 200mm, and a drying rate of 1.1g / h.

Claims

1. A method for preparing a moisture wicking composite special-shaped nylon 6 fiber, characterized in that: Nylon 6 slices are used as the core material, and nylon 6 moisture-wicking masterbatch is used as the skin material. After the fibers are formed by the skin-core composite spinning process, the fibers are sequentially soaked in a weak acid bath, a weak alkali bath, and a clean water bath, and then taken out and dried to obtain moisture-wicking composite special-shaped nylon 6 fibers. The pH value of the weak acid bath is greater than 5, and the temperature is 30~50℃; the pH value of the weak base bath is less than 9, and the temperature is 30~50℃; the pH value of the water bath is 7, and the temperature is 30~50℃; Nylon 6 suction and discharge masterbatch is made of nylon 6 chips, boron nitride and calcium carbonate as raw materials, which are blended and granulated by melt extrusion through a twin-screw extruder.

2. The method for preparing a moisture wicking composite special-shaped nylon 6 fiber according to claim 1, characterized in that: The mass ratio of the skin layer raw material to the core layer raw material is 10~30:70~90.

3. The method for preparing a moisture wicking composite special-shaped nylon 6 fiber according to claim 1, characterized in that: The spinning process parameters are: spinning temperature 240~270℃, spinning speed 4500~6000 m / min, side blowing temperature 15~25℃, side blowing speed 0.3~0.8m / s, and oiling rate 0.6~1.2%.

4. The method for preparing a moisture wicking composite special-shaped nylon 6 fiber according to claim 1, characterized in that: The weak acid bath is an acetic acid bath, a citric acid bath or a formic acid bath, and the fiber is immersed in the weak acid bath for 10 to 30 seconds; The weak alkali bath is an ammonia bath, a sodium bicarbonate bath or a triethanolamine bath, and the fiber is immersed in the weak alkali bath for 10 to 30 seconds; The fiber is immersed in the water bath for 60 to 120 seconds; The drying temperature is 80~100℃.

5. The method for preparing a moisture wicking composite shaped nylon 6 fiber according to claim 1, characterized in that: The specific preparation process of nylon 6 suction and discharge masterbatch is as follows: according to the mass proportions, 72-90 parts of nylon 6 chips, 5-10 parts of boron nitride, 5-15 parts of calcium carbonate and 0-3 parts of dispersant are put into a high-speed mixer and mixed evenly; the evenly mixed materials are added into a twin-screw extruder for melt extrusion granulation to obtain nylon 6 suction and discharge masterbatch.

6. The method for preparing a moisture wicking composite special-shaped nylon 6 fiber according to claim 5, characterized in that: The speed of the high speed mixer is 500~1000rpm, the mixing time is 5~20min; the extrusion temperature is 200~270℃.

7. The method for preparing a moisture wicking composite special-shaped nylon 6 fiber according to claim 5, characterized in that: The average flake diameter of boron nitride is 1~2μm and the thickness is 10nm; The average particle size of calcium carbonate is 80nm; The dispersant is one or more of ethylene bisstearic acid amide, ethylene acrylic acid copolymer and ethylene acrylic acid copolymer zinc salt ionomer.

8. A moisture wicking composite special-shaped nylon 6 fiber prepared by the method according to any one of claims 1 to 7, characterized in that: The cross section of the cortex is "three-leaf", "cross" or "five-leaf", and the cross section of the core layer is circular.

9. The moisture wicking composite shaped nylon 6 fiber according to claim 8, characterized in that: The breaking strength is 3.70~3.75cN / tex, the number of micropores per unit area on the fiber surface is 80~120, the deviation of the micropore size does not exceed 10%, and the unit area refers to 2μm×2μm.

10. The use of a moisture wicking composite special-shaped nylon 6 fiber as claimed in claim 8 or 9, characterized in that: Used to weave fabrics; The water absorption rate of the fabric is 270~290%, the drip diffusion time is 0.2~0.6s, the wicking height is 180~220mm, and the drying rate is 0.8~1.3g / h.

Citation Information

Patent Citations

  • Antibacterial moisture-transfer chinlon 6 and preparation method thereof

    CN102677215A

  • Preparing method for moisture absorbing and sweat releasing functional polyester fibers

    CN105332089A

  • Hydrophilic hygroscopic and sweat-releasing polyester fiber and preparation method thereof

    CN103320889A

  • Multifunctional fiber with moisture absorption and perspiration, antibacterial and heating functions and preparation method of multifunctional fiber

    CN106835348A

  • Electric and thermal conductive polymer fiber and preparation method thereof

    CN107254775A

Cited By

  • Moisture absorption and sweat releasing fiber and preparation method thereof

    CN120505716A

  • Water-repellent chinlon fabric and preparation method thereof

    CN120797248A

  • Light-absorbing and heat-emitting polylactic acid fiber as well as preparation method and application thereof

    CN121473033A